Systematic review and meta-analysis of non RCT's on health related quality of life after radical cystectomy using validated questionnaires: Better results with orthotopic neobladder versus ileal conduit. Issue 3 (March 2016) - Cerruto, M.A.; D'Elia, C.; Siracusano, S.; Gedeshi, X.; Mariotto, A.; Iafrate, M.; Niero, M.; Lonardi, C.; Bassi, P.; Belgrano, E.; Imbimbo, C.; Racioppi, M.; et al.
Abstract: Purpose: The current literature on the impact of different urinary diversions on patients' health related quality of life (HR-QoL) showed a marginally better quality of life scores of orthotopic neobladder (ONB) compared to ileal conduit (IC). The aim of this study was to update the review of all relevant published studies on the comparison between ONB and IC. Materials and methods: Studies were identified by searching multiple literature databases, including MEDLINE, CINAHL, the Cochrane Library, PubMed Data were synthesized using meta-analytic methods conformed to the PRISMA statement. Results: The current meta-analysis was based on 18 papers that reported a HR-QoL comparison between IC and ONB using at least a validate questionnaire. Pooled effect sizes of combined QoL outcomes for IC versus ONB showed a slight, but not significant, better QoL in patients with ONB (Hedges' g = 0.150; p = 0.066). Patients with ileal ONB showed a significant better QoL than those with IC (Hedges' g = 0.278; p = 0.000); in case series with more than 65% males, ONB group showed a slight significant better QoL than IC (Hedges' g = 0.190; p = 0.024). Pooled effects sizes of all EORTC-QLQ-C30 aspects showed a significant better QoL in patients with ONB (Hedges' g = 0.400; p = 0.0000). Conclusions: This meta-analysis of not-randomized comparative studies on the impact of different types of urinary diversions on HR-QoL showed demonstrated a significant advantage of ileal ONB compared to IC in terms of HR-QoL.